The effect of environmental, social, and governance (ESG) disclosure and shariah-compliance on firm performance among listed firms in Malaysia - Nik Asni, Nik Nur Farahiyah; Azmi, Nurul Azlin; Raja Ahmad, Raja Adzrin (UiTM Cawangan Johor, 2024)
This study aims to examine the effect of environmental, social, and governance (ESG) disclosure and Shariah-compliance status on firm performance and if the relationship between ESG disclosure and firm performance is moderated by Shariah-compliance status. Data on ESG disclosure and firm performance from 2020-2023 were sourced from Eikon DataStream. Shariah compliance status was hand-collected from the Securities Commission Malaysia's website. This study employs a regression model to test the hypotheses. We identify a significant positive relationship between ESG disclosure and Shariah-compliance status on firm performance. Additionally, the results also found that Shariah compliance status strengthens the positive relationship between ESG disclosure and firm performance. Our study contributes to the understanding of stakeholders, authorities, decision-makers, and academics regarding how ESG disclosure affects a firm's performance. These results also gave investors more insight into the importance of ESG considerations when making investment decisions for Sharia-compliance firms. The results, which corroborate the link between ESG disclosure and improved firm performance, ought to motivate managers to invest in ESG practices.